Longitudinal trajectories of emotions among athletes in sports competitions: Does emotional intelligence matter? - Levillain, G.; Martinent, G.; Vacher, P.; Nicolas, M. (Psychology of Sport and Exercise, 2022)
Objectives This research explored whether several subgroups of athletes representing distinct emotional trajectories could be shown to exist within the latent class growth analysis (LCGA) of pleasant and unpleasant sport emotions (anger, anxiety, dejection, excitement, happiness). A secondary aim was to explore whether athletes belonging to distinct emotional trajectories reported distinct scores of trait-emotional intelligence (EI) at time 1 (T1).